2020
DOI: 10.1016/j.marpetgeo.2020.104667
|View full text |Cite
|
Sign up to set email alerts
|

Influence of experimental temperature and duration of laboratory confined thermal maturation experiments on the evolution of the porosity of organic-rich source rocks

Abstract: Influence of experimental temperature and duration of laboratory confined thermal maturation experiments on the evolution of the porosity of organic-rich source rocks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…This may influence the evolution of the ultrafine structure of OM (nanoscopic structure of macerals in TEM and SEM images) and porosity during thermal maturation. For example, Cavelan et al, (2020a) showed that the duration and the temperature used during artificial maturations may influence the thermal degradation kinetics of OM and thus, the evolution of porosity. It is therefore possible that differences exist between the observations made on our experiments and the trend observed in sedimentary basins.…”
Section: Evolution Of the Ultrafine Structure Of Om During Oil And Gas Generationmentioning
confidence: 99%
“…This may influence the evolution of the ultrafine structure of OM (nanoscopic structure of macerals in TEM and SEM images) and porosity during thermal maturation. For example, Cavelan et al, (2020a) showed that the duration and the temperature used during artificial maturations may influence the thermal degradation kinetics of OM and thus, the evolution of porosity. It is therefore possible that differences exist between the observations made on our experiments and the trend observed in sedimentary basins.…”
Section: Evolution Of the Ultrafine Structure Of Om During Oil And Gas Generationmentioning
confidence: 99%
“…23 The effects of organic matter decomposition and expulsion on pore development in varied openness systems and duration under different pressure were studied by previous studies. 12,21,26 Open-system and semiclosed-system oil shale conversion experiments have investigated the optimal conditions for in situ conversion field retorting. 27,28 However, underground oil shale conversion occurred in confined pore space and closed hydrous pyrolysis is applicable to simulate pore structure evolution on the confined centimeter scale.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, detailed studies on petroleum generation and their pore structure evolution with increasing thermal maturity are significant for the in situ conversion process. The pyrolysis simulation is an important method for understanding pore evolution mechanisms in the source rock during thermal maturity, and the internal structure and pore space connectivity evolution directly control the hydrocarbon flow behavior through the pore channels . The effects of organic matter decomposition and expulsion on pore development in varied openness systems and duration under different pressure were studied by previous studies. ,, Open-system and semiclosed-system oil shale conversion experiments have investigated the optimal conditions for in situ conversion field retorting. , However, underground oil shale conversion occurred in confined pore space and closed hydrous pyrolysis is applicable to simulate pore structure evolution on the confined centimeter scale. , The pore network in lacustrine shale is mainly controlled by nanometer pores, , and these pores are mainly in the scope of the N 2 adsorption test . In this study, N 2 adsorption was tested before and after extraction for laminated and massive shale under different hydrocarbon generation stages by closed hydrous pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…A further understanding of the variation of the porosity of mudstones during maturation is necessary to predict the spots favorable for successful exploitation of shale oil and gas (Clarkson et al, 2013;Katz and Arango, 2018;Ross and Bustin, 2009). To better explain how OM composition and thermal maturity affect organic-rich mudstone porosity, laboratory thermal maturations were increasingly used these last years since they ensure to obtain rocks of different thermal maturity from the same initial immature sample (Cao et al, 2021;Cavelan et al, 2019aCavelan et al, , 2020aChen and Xiao, 2014;Guo et al, 2017;Han et al, 2019;Ko et al, 2016Ko et al, , 2018Song et al, 2020Song et al, , 2021Tan et al, 2021;T. Wang et al, 2021;Y.…”
Section: Introductionmentioning
confidence: 99%
“…Today several conventional and MBE (material balance equation) models used to estimate the gas sorption capacity of kerogen at different thermal maturity are still partly based on the knowledge acquired during these experiments (Alafnan, 2021;Alafnan et al, 2020;Ambrose et al, 2012;Ungerer et al, 2015). However, the experimental conditions (open, semi-confined, confined, the chosen duration/temperature, hydrous/anhydrous conditions, rock fabric) chosen for these maturations is known to influence OM thermal degradation processes (Behar et al, 2003;Cavelan et al, 2020a;İnan, 2000;Landais et al, 1994;Michels et al, 1995;Monthioux, 1988;Shao et al, 2018;Song et al, 2021;Suárez-Ruiz et al, 1994). The mineral phase, and especially clay minerals, is known to act as a support medium of the OM and a catalyzer during its thermal transformations (Tannenbaum et al, 1986;Tannenbaum and Kaplan, 1985;Tissot and Welte, 2013).…”
Section: Introductionmentioning
confidence: 99%